Feasibility of Self-Programming of the Speech Processor Via Remote Assistant Fitting in Experienced Cochlear Implant Users - Samuel-Sierra, Paola Angelica; Goffi-Gomez, Maria Valéria Schimidt; Magalhães, Ana Tereza de Matos; Bento, Ricardo Ferreira; Tsuji, Robinson Koji (International Archives of Otorhinolaryngology, 2025)
Introduction Adults with cochlear implants (CIs) need periodic programming of their speech processors to take advantage of alternative adjustments. However, this requires patients to attend the CI center in person.Objectives To evaluate the feasibility of speech processor (SP) self-programming with remote assistance in CI users. To establish the characteristics of those who could benefit from self-programming.Methods Adults with at least 1 year of experience with their CI, and whose SP was compatible with the use of the remote assistant fitting (RAF) were selected. Maps were created by the RAF from the neural response telemetry (NRT) results, evaluated in the same session with the audiologist. Patients were given 15-days to adjust to either the routine map or the NRT-based one. In the next session, the minimum and maximum stimulation levels (T- and C-levels) of all the maps were compared.Results No statistical difference was found when comparing the T- and C-levels of the map in use, the map adjusted by RAF, and the NRT-based map created by the RAF and adjusted by the patient.Conclusion Self-programming of the SP was safe and feasible in the studied sample of adults, since T- and C-levels were similar between the behavioral and RAF-adjusted maps. We consider it advisable to use the RAF for patients who have insertion of electrodes and at least one functioning; as well as those who do not have changes in anatomy, nor motor and cognitive conditions that prevent RAF usage.
Keywords: cochlear implant; deafness; fitting; remote fitting; neural response telemetry